Identità versus identità. Una riflessione sulle identità e sulle rappresentazioni dell’Altro come supporto al pregiudizio e alla diseguaglianza nelle società “quasi-multietniche” - Malizia, Pierfranco (SocietàMutamentoPolitica, 2013)
This article is the result of a series of reflections that are able to retrace some of the key issues in fund of the relationship with the Other’s identity, a relationship that today may be to promote or affect in toto the possibility of multiculturalism,and the relationship identity-prejudice.